The effect of oxytetracycline on Theileria parva in vitro - Spooner, P.R. (Cambridge University Press, 1990)
When bovine peripheral blood leucocytes were infected withTheileria parvasporozoites, immediate treatment with oxytetracycline (OTC) inhibited the development of sporozoites to mature schizonts. The extent of inhibition was dependent on drug concentration and duration of treatment. Concentrations of 5μg/ml OTC, or higher, for 8 days completely inhibited the establishment of schizonts and their ability to transform host cells. A cytostatic effect on schizont-infected cell lines was found with three tetracyclines and was also demonstrated on uninfected lymphoblasts. The parasites were found to be sensitive t OTC during development to schizonts, but when mature and established within host cells, schizonts were not demonstrably affected. The infectivity of sporozoites and the binding of sporozoites to lymphocytes were not directly inhibited by OTC. The results may explain the action of tetracyclines when used prophylactically during immunization against East Coast fever, and also the reasons for the ineffectiveness of these drugs when used therapeutically during patent disease.